External finance, firm growth and the benefits of information disclosure: Evidence from Finland - Ari Hyytinen; Mika Pajarinen (The Research Institute of the Finnish Economy (ETLA), 2002)
In this paper we study the relation between firm-level disclosure quality and the availability of external finance to firms. Using data on Finnish firms that are mostly private and small, we first estimate `excess growth' made possible by external finance. We then show that the excess growth is associated with the quality of disclosure, and that at least a part of the association arises because firms with excess growth self-select. Interestingly, the association also seems to be related to a priori financially constrained firms. The results suggest that (a) the firms that resort to high quality disclosure are more likely to be the ones that grow at a rate that requires external finance and (b) that the excess growth and the choice of disclosure quality are jointly determined.
Keywords: 330; Corporate finance; information disclosure; auditing; financial constraints; Unternehmensfinanzierung; Asymmetrische Information; Unternehmenswachstum; Publizitätspflicht; Finnland